The Effect of Coworker Support and Incentives on Employee Productivity of PT PLN (PERSERO) Service Implementation Unit Costumer (UP3) Banda Aceh - Syarifah, Syarifah Mauli Masyithah; T. Muhammad Jumeil; Nurrahmad; Leni Marlina (Institut Agama Islam Negeri Lhokseumawe, 2025)
This research aims to analyze the influence of support from colleagues from the same profession and incentives on employee productivity at PT PLN (Persero) UP3 Banda Aceh. The sample size for this research was 81 employees. The results of the partial test research showed that the support variable from co-workers in the same profession had an influence on the productivity of PT PLN (Persero) UP3 Banda Aceh employees. Incentive variables influence employee productivity at PT PLN (Persero) UP3 Banda Aceh. Then the Simultaneous Test between the variables of support from co-workers in the same profession and incentives influences the productivity of PT PLN (Persero) UP3 Banda Aceh employees. Partially, the support of colleagues from the same profession influences the productivity of PT PLN (Persero) UP3 Banda Aceh employees with a value of tcount (3,285) which is greater than ttable (1,6449). Partially, incentives have an effect on the productivity of PT PLN (Persero) UP3 Banda Aceh employees with a value of tcount (2,876) which is greater than ttable (1,6449). Simultaneously, the support of colleagues from the same profession and incentives influence the productivity of PT PLN (Persero) UP3 Banda Aceh employees with a value of Fcount (21,192) greater than Ftable (3,00).